Respuesta :

Answer: (2, 5)

Step-by-step explanation:

y = 2x + 1 y = 4x − 3

Eliminate the equal sides of each equation and combine.

2x + 1 = 4x − 3

Solve 2x + 1 = 4x − 3 for x.

Move all terms containing x to the left side of the equation.

Subtract 4x from both sides of the equation.

2x + 1 − 4x = −3

Subtract 4x from 2x.

−2x + 1 = −3

Move all terms not containing x to the right side of the equation.

Subtract 1 from both sides of the equation.

−2x = −3 − 1

Subtract 1 from −3.

−2x = −4

Divide each term by −2 and simplify.

x = 2

Evaluate y when x = 2.

Substitute 2 for x. y = 4 (2) − 3

Simplify 4 (2) − 3.

Multiply 4 by 2.

y = 8 − 3

Subtract 3 from 8.

y = 5

The solution to the system is the complete set of ordered pairs that are valid solutions.

(2, 5)

The result can be shown in multiple forms.

Point Form:

(2, 5)

Equation Form:

x = 2, y = 5

Ver imagen drazo18